Road Vehicles Surroundings Supervision: On-Board Sensors and Communications - Felipe Jimenez (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue presents a selection of current solutions for vehicle surroundings perception systems. This perception is essential for many advanced driver application systems and autonomous driving, and there are currently several challenges that need addressing. Perception can be obtained using on-board sensors, but, due to their limitations, the development of sensor fusion techniques or specific algorithms is needed. Vehicle positioning is also important, but further refined accuracy and specific requirements arise with each new application. Apart from on-board sensors, wireless communication can provide information from a larger electronic horizon that can be used for better decision making. Finally, all this information can be used to enhance development of autonomous driving